Comparing the efficacy of endoscopic endonasal versus microscopic transsphenoidal approach for the management of sellar and suprasellar tumors: a systematic review and meta-analysis protoco - Tango, Tamara; Daniel, Jeremiah Oluwatomi Itodo; Mugenyi, Nathan; Abongha, Gobti Beltus; Mesfin, Samuel; Javed, Saad; Omran, Murad Othman; Eltingary, Mazin M.; Kyaruzi, Victor Meza (Journal of Surgical Protocols and Research Methodologies, 2023)
Managing sellar and suprasellar tumors is challenging due to their diverse origins and proximity to critical structures. The transsphenoidal surgical approach has become the preferred method, evolving from transcranial attempts to reduce morbidity. Microscopic transsphenoidal techniques have been refined over time, with endoscopic endonasal surgery emerging as a significant advancement. Due to the multifaceted nature of these approaches, the complexities of the pathology and the paucity of data from specific regions, understanding the prevalence, characteristics and management outcomes of sellar and suprasellar tumors is crucial for informing healthcare practices and resource allocation. This study aims to collate evidence-based insights into the efficacy of the endoscopic endonasal approach compared with the microscopic transsphenoidal approach as a surgical intervention for sellar and suprasellar tumors, following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines for 2020. To source pertinent information,we will rely on four primary central databases: PubMed ,EMBASE,SCOPUS and the Cochrane Central Registerof Controlled Trials.Theprimaryoutcomemeasurewillbethesurgicaloutcome’seffectivenessinachievingtumorresectionandpreservingpituitary function. The study protocol is duly registered with the International Prospective Register of Systematic Reviews (PROSPERO), with no requirement for ethical approval as it exclusively relies on previously published research. We aim to publish our findings in scientific journals and present the abstract at conferences to guide clinical practice
Keywords: Sellar and suprasellar tumors; Endoscopy; Surgery